Strengthening Human Resources of Msmes And Cooperatives Through Counseling and Joint Dialogue In Cianjur Regency - Sudadi Pranata; Erna Susilawati; Amroni Amroni; Angky Febriansyah; Nandang Komara; Ai Musrifah; M Yani Syafeí; Rahma Wahdiniwaty (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Strengthening human resources (HR) in the MSME and cooperative sectors is an important aspect of enhancing local economic competitiveness, including in Cianjur Regency. MSMEs and cooperatives as main drivers of the people's economy often face various obstacles such as weak managerial capabilities, limited financial literacy understanding, and restricted use of digital technology in running their businesses. These problems cause productivity and business sustainability to be less than optimal. To address these issues, a Community Service activity titled “Strengthening MSME and Cooperative HR through Counseling and Joint Dialogue in Cianjur Regency” was carried out by lecturers and students from several universities in Indonesia. The activities were conducted through counseling methods, group discussions, and interactive dialogues involving MSME actors, cooperative administrators, regional officials, and relevant stakeholders. The materials delivered included business management, financial literacy, digital marketing strategies, and strengthening partnership networks between business actors and supporting institutions. This Community Service activity was enthusiastically attended by participants who gained new understanding in managing businesses professionally, innovatively, and adaptively to digital development. This program is expected to increase the capacity of MSME and cooperative HR, strengthen collaboration among economic actors, and encourage the creation of economic independence and community welfare in Cianjur Regency sustainably.